An optimized configuration of adsorptive wells for the remediation of an aquifer contaminated by multiple aromatic hydrocarbon pollutants - Bortone, Immacolata; Chianese, Simeone; Erto, Alessandro; Nardo, Armando Di; Crescenzo, C. de; Karatza, Despina; Santonastaso, Giovanni Francesco; Musmarra, Dino (Elsevier, 2019)
Adsorptive wells arrays are an innovative outline of Permeable Reactive Barrier (PRBs) made of a definite number of passive deep wells opportunely distributed in the aquifer, known as PAB-D (Discontinuous Permeable Adsorptive Barrier). They are generally located downstream the contaminated groundwater flow and perpendicularly to the groundwater flow direction. Being PAB-D wells filled with adsorbing media, whose hydraulic permeability is higher than the surrounding media, the array will create a targeted capture zone, which will force the contaminated water to pass through the whole PAB-D, allowing for both the interception of the contaminant plume and its treatment. In this work, an optimized configuration of PAB-D is presented, for the in situ-remediation of an aquifer simultaneously contaminated by benzene and toluene. The design optimization of the PAB-D was performed by using COMSOL Multiphysics®, in which numerical simulations reproduced the transport and the adsorptive phenomena occurring inside the aquifer and the barrier itself. The proposed technique was applied to the remediation of an aquifer located in an urban area in the north of Naples (Italy), in proximity of numerous landfills, where the contamination was spread over an area of 0.10 km2. Simulation results confirm the effectiveness of the PAB-D, being both pollutant plumes intercepted and their concentrations reduced below their correspondent Italian regulatory threshold values. The best array configuration of PAB-D resulted made of 741 wells, each having a diameter of 0.6 m, which was also compared with a continuous barrier (PAB-C) showing a reduction of about 49% of the volume and 35% of the overall remediation cost.
Keywords: Permeable adsorptive barrier; Groundwater remediation; PRB; Organic pollutant removal; Optimization